Infantile and Juvenile Morbidity in Psychiatric Inpatients at Cienfuegos Province - Beatriz Sabina Roméu; Zenaida María Sáez; María Leyani Fuentes García; Niusha Imiya Hernández Muñoz; Daimí Sarmiento García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: Several studies have shown the rise in psychiatric disorders worldwide, either in children and youngsters, although these problems are not so evident to society as other health problems are . Objective: to determine the frequency of psychiatric disorders according to age and sex in children and adolescents. Methods: Descriptive, transversal cohort study developed to 1181 patients who were admitted with psychiatric disorders at the psychiatric hospital from Cienfuegos province from the year 2004 to 2008, both included. Results: 65,8 % of the patients were females and 79,5 % of them were adolescents. Suicide attempt represented half 50,9 % of all the diagnostic cases. 61,7% of them belonged to the age group 11 to 14 years of age and equal percentage to the age group that included ages 15 - 18, being females 66,6% of these cases . 31,7 % of the preschoolers suffered from hyperkinetic disorders and 34 % of the school children presented with emotional disturbances. There was an annual mean of 236,5 hospital admissions. Conclusions: Suicide attempt as the first cause of psychiatric hospital admission, mainly in female adolescents is the most highlighting mental health problem at the Infantile and Juvenile Psychiatric Service in Cienfuegos province.